The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/abbs/gmw092
|View full text |Cite
|
Sign up to set email alerts
|

Ascl1 represses the mesendoderm induction in <italic>Xenopus</italic>

Abstract: Ascl1 is a multi-functional regulator of neural development in invertebrates and vertebrates. Ectopic expression of Ascl1 can generate functional neurons from non-neural somatic cells. The abnormal expression of ASCL1 has been reported in several types of carcinomas. We have previously identified Ascl1 as a crucial maternal regulator of the germ layer pattern formation in Xenopus Functional studies have indicated that the maternally-supplied Ascl1 renders embryonic cells a propensity to adopt neural fates on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Together, these studies imply that KdPT, similar to KPV or α‐MSH, acts via NF‐κB inhibition to induce a tolerogenic DC phenotype. As α‐MSH inhibits the maturation of human monocyte‐derived DC and importantly maintains the tolerogenic phenotype via the upregulation of the anti‐inflammatory protein annexin A1, KdPT might act similarly as we observed increased annexin A1 mRNA levels in DC from KdPT‐treated mice and in KdPT‐stimulated HLA‐DR + cells from individuals with psoriasis.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Together, these studies imply that KdPT, similar to KPV or α‐MSH, acts via NF‐κB inhibition to induce a tolerogenic DC phenotype. As α‐MSH inhibits the maturation of human monocyte‐derived DC and importantly maintains the tolerogenic phenotype via the upregulation of the anti‐inflammatory protein annexin A1, KdPT might act similarly as we observed increased annexin A1 mRNA levels in DC from KdPT‐treated mice and in KdPT‐stimulated HLA‐DR + cells from individuals with psoriasis.…”
Section: Discussionmentioning
confidence: 56%
“…d,e), all markers associated with tolerogenic and immunosuppressive DC functions as well as the DC‐mediated Treg expansion . At least in monocyte‐derived DC, it has been demonstrated that the induction of a tolerogenic phenotype by α‐MSH was mediated via the increased expression of annexin A1 . Therefore, we quantified annexin A1 in MHC‐II + CD19 − cells from regional lymph nodes of KdPT‐, BMDP‐ and PBS‐treated mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Ascl1 (achaete-scute family bHLH transcription factor 1), aliases ASCL1 and ASH1, is a multi-functional regulator of neural development in invertebrates and vertebrates, whereas the ectopic expression of Ascl1 can generate functional neurons from non-neural somatic cells. Functional studies have identified Ascl1 as a crucial maternal regulator of the germ layer pattern formation in clawed frogs, since the maternally expressed proteins can establish the major embryonic body axes and a pre-patterned transitional stage for later-acting zygotic signals (Gao et al, 2016;Min et al, 2016). Previous studies have revealed that the maternally supplied Ascl1 was capable to set a pre-patterning tendency for frog embryonic cells to adopt neural fates and represses the mesendoderm formation via the HDAC-dependent antagonism of frog VegT (Gao et al, 2016;Min et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies have identified Ascl1 as a crucial maternal regulator of the germ layer pattern formation in clawed frogs, since the maternally expressed proteins can establish the major embryonic body axes and a pre-patterned transitional stage for later-acting zygotic signals (Gao et al, 2016;Min et al, 2016). Previous studies have revealed that the maternally supplied Ascl1 was capable to set a pre-patterning tendency for frog embryonic cells to adopt neural fates and represses the mesendoderm formation via the HDAC-dependent antagonism of frog VegT (Gao et al, 2016;Min et al, 2016). On the other hand, the hairy genes are key bHLH transcription factors required in the early neural crest development of clawed frogs (Vega-López et al, 2015), whereas neural crest formation is one of the fundamental processes in the early stages of the frog embryonic development to generate a variety of tissues and cell types.…”
Section: Discussionmentioning
confidence: 99%